Spraying humic acid regulator on cultivated Codonopsis pilosula (Franch.) Nannf. to improve yield of active constituents - Huang, Gaojian; Miao, Huifeng; Chen, Yaqian; Wang, Ke; Zhang, Qiang; Yang, Zhiping (Frontiers in Plant Science, 2024)
Plant growth regulators have been used in the cultivation of medicinal plants to increase yield, but the existing regulators decreased the content of active constituents which benefit human health. Therefore, it is necessary to find a new growth regulator to achieve the win-win goal of increasing yield and improving active constituents' accumulation. The potential of replacing chlorocholine chloride with a new humic acidbased growth regulator was evaluated by measuring the yield and active constituents' accumulation of Codonopsis pilosula. Three treatments including water (CK), chlorocholine chloride (T1) and humic acid regulator (T2) were applied by foliar spraying. Among them, both chlorocholine chloride and humic acid regulator belong to biostimulant. The result showed that the root yield in T1 and T2 were significantly increased by 59.1% and 54.9% compared with CK, respectively, and there was no significant difference between T1 and T2. Compared with CK, the yields of lobetyolin, syringin and atractylenolide Ⅲ of Codonopsis pilosula were significantly decreased by 6.3%, 7.3% and 13.0% in T1, but were significantly increased by 22.8%, 14.8% and 32.0% in T2, respectively. Redundancy analyses showed that photosynthetic rate, sucrose phosphoric acid synthetase and phosphomannomutase had higher degree of explanation for yield and quality. Linear regression results indicated that photosynthetic rate and phosphomannomutase were the main factors to affect yield and active constituents yields, respectively. In addition, the output-input ratios based on the yields of polysaccharides, lobetyolin, syringin and atractylenolide Ⅲ of Codonopsis pilosula in T2 was significantly increased by 6.5%, 15.2%, 8.7% and 31.2% respectively as compared with T1. Overall, compared with water treatment, both chlorocholine chloride and humic acid regulator treatments can increase the root yield of Codonopsis pilosula. Compared with chlorocholine chloride, humic acid regulator can improve the yield of active constituents and economic benefits of Codonopsis pilosula. This study indicated that reasonable selection of plant growth regulators is of great significance for achieving a win-win goal of increasing the root yield and active constituents of medicinal plants.